Organ speak : what it really means to listen to our bodies - Enders, Giulia (HarperOne, 2026)
In a world that is becoming ever louder and more complex, sometimes the best perspective is to look inward--at our own physicality. For thousands of years, our bodies have faced challenges and found their own unique ways to overcome them. What can we learn from these extraordinarily complex beings?